KEY PERFORMANCE INDICATORS FOR MEASURING SUSTAINABILITY IN HEALTH CARE INDUSTRY IN MALAYSIA - Saiful Bahri, Mohamed; K.L., Wong; K. E., Chong (2018)
The health care industry in Malaysia was the fastest-growth industry over the past few years. In today’s competitive business environment, companies focus on improving sustainability to reduce cost and improve well-being of the environment and society. However, there are limited published studies on the evaluation of sustainability performance for the healthcare sector. This paper aims to formulate a list of key performance indicators (KPI) for the sustainability performance. First, a literature study of KPIs from various industries was carried out. Next, an in-depth meeting was conducted to gain insights and feedbacks with the management of a private hospital. Finally, a set of 70 KPIs which can be used for measuring sustainability performance in health care industry was developed. These 70 KPIs were used to design a questionnaire which is then distributed to the private hospital.